Exploring Contact Toxicity of Essential Oils against Sitophilus zeamais through a Meta-Analysis Approach - Fernanda Achimón; Maria L. Peschiutta; Vanessa D. Brito; Magalí Beato; Romina P. Pizzolitto; Julio A. Zygadlo; María P. Zunino (Plants, 2022)
Sitophilus zeamais is a primary pest of maize. Our aim was to perform a qualitative review and meta-analyses with 56 scientific articles published from 1 January 2000 to 1 October 2022 dealing with direct (topical application) and indirect (impregnation of essential oils, EOs, onto filter paper or maize grains) contact toxicity of EOs against S. zeamais. Three independent meta-analyses of single means of LD50 (direct contact) and LC50 (indirect contact) were conducted using a random effect model. Essential oils more frequently evaluated were those belonging to Asteraceae, Apiaceae, Lamiaceae, Myrtaceae, Piperaceae, and Rutaceae. The LC50 global mean values were 33.19 µg/insect (CI95 29.81–36.95) for topical application; 0.40 µL/cm2 (CI95 0.25–0.65) for filter paper indirect contact; and 0.50 µL/g maize (CI95 0.27–0.90) for maize grains indirect contact. The species Carum carvi, Salvia umbratica, Ilicium difengpi, Periploca sepium, Cephalotaxus sinensis, Murraya exotica, Rhododendron anthopogonoides, Ruta graveolens, Eucalyptus viminalis, Ocotea odorifera, Eucalyptus globulus, Eucalyptus dunnii, Anethum graveolens, Ilicium verum, Cryptocarya alba, Azadirachta indica, Chenopodium ambrosioides, Cupressus semperivens, Schinus molle, Piper hispidinervum, Mentha longifolia, and Croton pulegiodorus showed LC50 or LD50 values lower than the global means, indicating good insecticidal properties. Our results showed that EOs have great potential to be used as bioinsecticides against S. zeamais.